Sosialisasi Gerakan Perilaku Hidup Bersih dan Sehat (PHBS) di SDN 054945 Desa Dogang Kecamatan Gebang Kabupaten Langkat (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
Health education at the elementary school level represents a long-term investment in developing a stronger and more capable generation. By fostering a proper understanding from an early age, children are expected to build a resilient defense against various health threats. This community service program aims to broaden the knowledge and awareness of students at SDN 054945 Dogang Village, Gebang District, Langkat Regency, North Sumatra, regarding Clean and Healthy Living Behavior (known as PHBS). As a promotive and preventive strategy, PHBS is essential to instill from childhood to cultivate healthy habits and prevent various health disorders. This study utilizes a qualitative approach, applying the Miles and Huberman interactive analysis model. The activity, conducted on July 20, 2024, involved 77 fourth and fifth-grade students and followed three main stages: preparation, implementation, and evaluation. Socialization was carried out interactively through handwashing tutorial videos, physical exercises, PHBS-themed songs and rhythmic clapping, and Q&A sessions. The results indicated an improvement in students' understanding of various PHBS indicators, including handwashing habits, waste management, healthy food consumption, physical activity, growth monitoring, avoiding tobacco smoke, maintaining toilet cleanliness, and eradicating mosquito larvae. The active participation shown by the students reflects a heightened awareness of practicing PHBS within the school environment. In conclusion, this educational initiative has delivered a positive impact on student knowledge and holds the potential to foster a sustainable culture of clean and healthy living, both at school and in their daily lives.